2019
DOI: 10.3390/cells8121540
|View full text |Cite
|
Sign up to set email alerts
|

From Endogenous to Synthetic microRNA-Mediated Regulatory Circuits: An Overview

Abstract: MicroRNAs are short non-coding RNAs that are evolutionarily conserved and are pivotal post-transcriptional mediators of gene regulation. Together with transcription factors and epigenetic regulators, they form a highly interconnected network whose building blocks can be classified depending on the number of molecular species involved and the type of interactions amongst them. Depending on their topology, these molecular circuits may carry out specific functions that years of studies have related to the process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 189 publications
(341 reference statements)
0
15
0
Order By: Relevance
“…Noncoding short microRNAs (miRNA; 18-25 nucleotides) are present, both intra-and extracellularly, in different body fluids of humans and animals (Ferro et al, 2019;Matsuyama and Suzuki, 2019). They can have very different biological functions, including regulation of genes (Miller and Wahlestedt, 2010;Melnik and Schmitz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Noncoding short microRNAs (miRNA; 18-25 nucleotides) are present, both intra-and extracellularly, in different body fluids of humans and animals (Ferro et al, 2019;Matsuyama and Suzuki, 2019). They can have very different biological functions, including regulation of genes (Miller and Wahlestedt, 2010;Melnik and Schmitz, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA mediated regulation could serve to manage the impact of noise in gene expression. 91 A number of studies have addressed the relationship between miRNA and noise, and the results suggested that miRNAs could provide precision to protein expression by buffering noise when needed or exploit stochasticity in biological contexts that take advantage of gene expression variability, such as differentiation processes. 91 The coherent, quite uniform variations of the miRNAs in our work appear to be in line with this.…”
Section: Discussionmentioning
confidence: 99%
“…Noncoding short microRNAs (miRNA) are both intra-and extra-cellular and are found in different body fluids of mammals [53,54]. They regulate up to several hundred genes and have many other, different biological functions [55,56].…”
Section: Introductionmentioning
confidence: 99%